Uric Acid Causes Pancreatic β Cell Death and Dysfunction via Modulating CHOP-Mediated Endoplasmic Reticulum Stress Pathways - Xueyan Li; Yunan Chen; Lei Su; Jialin He (Diseases, 2025)
Background: Uric acid has been proposed as a diabetogenic factor while its effect on pancreatic β cell function remains elusive. This study aimed to explore the impact of uric acid levels on β cell function and delineate its underlying molecular mechanisms. Methods: Both in vivo hyperuricemia diet-induced mouse models and in vitro pancreatic β cell models were utilized. Results: A progressive decrease in glucose-stimulated insulin secretion and increase in β cell apoptosis were observed in the hyperuricemia diet-induced mouse model, and these could be effectively restored by urate-lowering therapy. The dose- and time-dependent direct effects of uric acid on β cell apoptosis and insulin secretion were further confirmed in both INS-1E cells and primary isolated islets. Mechanistically, the primary role of expression of the endoplasmic reticulum stress marker C/EBP homologous protein (CHOP) was detected by RNA sequencing, and the inflammatory factor NLRP3 and pro-apoptotic genes were significantly upregulated by uric acid treatment. Conclusions: Together, our findings indicate a direct crosstalk between uric acid and β cells via CHOP/NLRP3 pathway, providing a new understanding of the diabetogenic effect of uric acid.